Is Short-Term Debt a Substitute or a Complement to Good Governance? - Anginer, Deniz; Demirguc-Kunt, Asli; Tepe, Mete; Simsir, Serif Aziz (World Bank, Washington, DC, 2019)
Short-term debt exposes firms to credit supply shocks and liquidity risk. Short-term debt can also reduce potential agency conflicts between managers and shareholders by exposing managers to more frequent monitoring by the market. This paper examines whether internal monitoring through independent boards and stronger shareholder protections can substitute for external monitoring through the use of short-term debt. The analysis finds that the relationship between debt maturity and governance depends on shareholder rights in a given country. In countries with stronger investor protection, governance and short-term debt act as substitutes. Instrumenting the institutional environment with legal origin confirms the results.